Busan's Paradiplomacy: Aspiring to be the World's Premier Film City - Dermawan, Windy; Clarissa, Sarah; Affandi, RMT Nurhasan; Santoso, Rizal Budi; Jasuma, Nanda Blestri (Journal of Paradiplomacy and City Networks, 2023)
This study explored the image transformation of Busan, South Korea, from an industrial hub to a globally recognized City of Film. By employing a paradiplomacy framework, the research examined how Busan utilized BIFF as both a cultural event and a strategic tool for international diplomacy, economic development, and city branding. This qualitative research focused on gathering data largely through a comprehensive evaluation of scientific literature, including books and papers relevant to the case study. The analyses delved into the evolution of the BIFF event and its significant role in rebranding Busan from a declining industrial city to the first "City of Film" in Asia, a title bestowed by UNESCO. The study highlighted how the festival had successfully stimulated local economic growth, bolstered creative industries, and facilitated cultural exchange. The result demonstrated that BIFF had been pivotal in repositioning Busan as a significant player in the international film industry and a vibrant cultural destination. In conclusion, Busan's status as Asia's "City of Film" should be sustained, and the ongoing significance of integrating cultural initiatives with wider urban development strategies should also be emphasized.